Arrantly Absent: Atheism in Psychological Science From 2001 to 2012 Ψ. (July 2014) - Brewster, Melanie E.; Robinson, Matthew A.; Sandil, Riddhi; Esposito, Jessica; Geiger, Elizabeth
This study provides a content analysis of the past 12 years (2001-2012) of academic scholarship about atheism and atheist individuals from a social scientific lens in the United States. The content analysis yielded 100 articles across disciplines including psychology, sociology, religious studies, and political science. Although the number of articles about atheism published since 2001 has increased steadily per year ( n = 0 in 2001 compared with n = 20 in 2012), the topics discussed in the atheism literature were narrow in scope and involved (a) comparing religious/spiritual (R/S) belief systems to atheism or (b) discussing bias against atheists. In addition, most of the articles were nonempirical (58%). Content analysis data suggest that atheism is an understudied topic in psychological science (31% of the total articles were from psychology), and discourse on atheism is often presented from cognitive and social-psychology perspectives, rather than a counseling psychology lens. Only a handful of the total articles centered on topics related to mental health (e.g., psychological distress and well-being) or counseling and training; however, such studies suggested that atheists have comparable levels of mental health to R/S people, a conclusion that contradicts most prior research on R/S and psychological well-being. Findings from this content analysis suggest that atheist individuals are an underserved and understudied group that would benefit from advancements in counseling psychology scholarship specific to their experiences.